Adapting epicutaneous patch testing protocols to assess immediate‐type skin reactions. (25th June 2020) - Mehling, A.; Benard, S.; Braun, N.; Degwert, J.; Duttine, M.; Jassoy, C.; Merk, H.; Rossow, U.; Welzel, J.; Wigger‐Alberti, W.; Wilhelm, K.P.; Ennen, J.
Abstract: Objective: During the development of cosmetic formulations, in vitro and in vivo methods are essential tools used to reliably assess the skin irritation potential of a product or ingredient. Epicutaneous patch testing (single and/or multiple application protocols) has long been used as an initial in vivo method to screen for possible skin irritation properties of a substance or formulation. To confirm the mildness and dermatological and/or consumer acceptance of a product, use tests are often subsequently conducted. A study was therefore initiated to see how well patch test results correlate with use tests with respect to irritation elicited by skincare (leave‐on) products. Methods/results: A number of different cosmetic formulations were assessed in both tests. Although the patch test results did not indicate substantial irritation potentials, immediate‐type reactions (stinging and redness) were observed in some volunteers which disappeared within approx. 1 h. Although transient, these reactions suggested that consumer acceptance would probably be low and the studies were discontinued. Immediate‐type reactions are rare but have been described for some substances used in cosmetics. These unexpected results were nevertheless intriguing and prompted the start of a journey to see if patch test protocols could be modified to assess these reactions. An occlusive short‐term patch test protocol with an application period of 20 min was developed. Successful identification of the spontaneous reactions became possible. Furthermore, there was a correlation between the intensity of reactions observed in the short‐term patch test and those observed in the controlled in‐use studies. Short‐term patch testing using the developed protocol can therefore reliably be used as a screening method, for example in the development and optimization of cosmetic formulations containing ingredients that could cause spontaneous reactions, for instance of non‐immunological contact urticaria type. Conclusion: The lessons learned from this studies indicate that simple modifications of existing test protocols can lead to important insights into skin reactions. These modifications can then be used to create further building blocks in the development and optimization of test strategies for cosmetic formulations which offer reliable study designs for possible reactions product developers may encounter. Abstract : Although the 24‐h epicutaneous patch testing is routinely used as a screening method in the development and optimization of cosmetic formulations, it does not allow all reactions to be assessed and surprises can be encountered. A number of ingredients can cause spontaneous although transient reactions, such as redness possibly indicative of reaction such as non‐immunological contact urticaria. As these reactions are transient and usually reside resolve within 1–2 h, typical ECT protocols do not allow detection of immediate‐type reactions, but simple modifications of existing test protocols can lead to important insights into skin reactions. Résumé: Objectif: Lors du développement de formulations cosmétiques, les méthodes in vitro et in vivo sont des outils essentiels utilisés pour évaluer de manière fiable le potentiel d'irritation cutanée d'un produit ou d'un ingrédient. Le test épicutané (protocoles d'application uniques et / ou multiples) est utilisé depuis longtemps comme méthode initiale in vivo pour dépister les éventuelles propriétés d'irritation cutanée d'une substance ou d'une formulation. Afin de confirmer la douceur et l'acceptation dermatologique et / ou consommateur d'un produit, des tests d'usage sont souvent effectués ultérieurement. Une étude a donc été initiée pour voir dans quelle mesure les résultats des tests épicutanés correspondent aux tests d'usage en ce qui concerne l'irritation provoquée par les produits de soin (sans rinçage). Méthodes/Résultats: Un certain nombre de formulations cosmétiques différentes ont été évaluées dans les deux tests. Bien que les résultats du test épicutané n'indiquent pas de potentiels d'irritation substantiels, des réactions de type immédiat (picotements et rougeurs) ont été observées chez certains volontaires. Celles‐ci ont disparu en à peu près 1 heure. Bien que transitoires, ces réactions de type 5 suggéraient que l'acceptation du consommateur serait probablement faible et les études ont été interrompues. Les réactions de type immédiat 6 sont rares mais ont été évoquées en relation avec certaines substances utilisées en cosmétique. Ces résultats inattendus étaient néanmoins intrigants et ont incité le lancement d'un processus pour voir si les protocoles de test épicutané pouvaient être modifiés pour évaluer ces réactions. Un protocole de test épicutané à court terme occlusif avec une période d'application de 20 min a été développé, permettant l'identification réussie des réactions spontanées. Il a été de plus constate une corrélation entre l'intensité des réactions observées dans le test épicutané à court terme et celles observées dans les test d'usage contrôlés. Le test épicutané à court terme utilisant le protocole développé peut donc être utilisé de manière fiable comme méthode de dépistage, par exemple dans le développement et l'optimisation de formulations cosmétiques contenant des ingrédients qui pourraient provoquer des réactions spontanées, par exemple de type urticaire de contact non immunologique. Conclusion: Les leçons tirées de ces études indiquent que de simples modifications des protocoles de test existants peuvent révéler des informations importantes sur les réactions cutanées. Ces modifications peuvent ensuite être utilisées pour créer d'autres blocs de construction dans le développement et l'optimisation de stratégies de test pour des formulations cosmétiques qui offrent des conceptions d'études fiables pour les réactions possibles que les développeurs de produits peuvent rencontrer.